Evaluation Model of the Integrational Relationship between Knowledge Management Processes and Business Processes - Ulbinaitė, Aurelija; Gribovskis, Justas (Information & Media, 2020)
In a contemporary organization, knowledge management is rarely assumed to be a supportive activity. Knowledge management processes are rather assessed as being inseparable from other main organizational processes. Considering the up-to-date research, there are no doubts about the benefits of knowledge management. However, because of its wide internal and external dissemination, it is challenging to identify and assess its value both in its entirety and in its value created by its individual processes. In the interdisciplinary context of literature analysis of information and communication and management research, in this article, the authors present the integrative evaluation model of the relationship between knowledge management processes and business processes. The model is characterised by its wide organizational applicability and allows measuring the value created by knowledge management processes in a real business environment. The model integrates the processes of product development, manufacturing and sales, including their constitutional dimensions, metrics and indexes, respectively. All this enables determining the impact of knowledge management processes on the main business processes and the resulting organizational added value.
Keywords: knowledge management; knowledge management processes; organizational processes; product development; product manufacturing; product sales; process evaluation; process integration